THE PROPORTION OF NEUTROPHILS TO LYMPHOCYTES IN THE CORONARY ARTERY DISEASE: AN OBSERVATIONAL RESEARCH USING A CROSS-SECTIONAL DESIGN (Journal of Pharmaceutical Negative Results, 2022)
Thirty percent of all deaths are attributed to cardiovascular disease. Annually, 17.3 million lives are lost due to this illness. 40 percent of all deaths from cardiovascular causes are attributable to coronary heart disease. This study aims to examine the correlation between neutrophils and lymphocytes as an indicator of inflammation by analysing clinical and laboratory data from persons with coronary artery disease. Seventy-two patients who were reported to the Medicine Department and who met the inclusion criteria were analysed. Participants were interviewed using a questionnaire that probed them on demographics, substance abuse, and the clinical profile. Medical histories from the past, present, and even the far past were all requested in the questionnaire. Sputum, blood, CSF, PL, AC, and pus cultures were taken from all patients. There was an increase in neutrophils (+22.6), lymphocytes (+27.6), platelets (+3.89), and the neutrophil-to-lymphocyte ratio (+0.99) among the average white blood cell count of 9.4 (+1.6) among 72 patients with coronary artery disease. Therefore, neutrophils and lymphocytes may serve as surrogate markers of coronary artery disease severity.